2019
DOI: 10.1002/cncr.32540
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of recurrence and metastasis in BRCA1/BRCA2‐associated breast cancers

Abstract: BACKGROUND: Breast cancer subtypes are associated with distinct metastatic patterns. Whether germline BRCA1/BRCA2 mutation status is independently associated with central nervous system (CNS) relapse, controlling for tumor subtype, is unknown. METHODS: Patients who were treated at Dana-Farber Cancer Institute and diagnosed with a first locoregional recurrence (LRR) or metastasis between 1981 and 2014 were identified using 2 institutional registries: 1) patients treated for recurrent breast cancer and 2) patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 53 publications
5
74
3
2
Order By: Relevance
“…Several studies have demonstrated that BRCA1-associated tumors are usually TNBC and BRCA2 mutation carriers commonly develop ER-positive breast cancer [43][44][45]. A similar pattern was reported in metastatic and recurrent breast cancer [46]. However, only a few reports have included age factors.…”
Section: Discussionmentioning
confidence: 76%
“…Several studies have demonstrated that BRCA1-associated tumors are usually TNBC and BRCA2 mutation carriers commonly develop ER-positive breast cancer [43][44][45]. A similar pattern was reported in metastatic and recurrent breast cancer [46]. However, only a few reports have included age factors.…”
Section: Discussionmentioning
confidence: 76%
“…However, BC subgroups with a higher TMB could be represented by TNBC [99] and g BRCA1/2 -mutated tumors, similar to what was observed with microsatellite unstable high (MSI-H) cases in colorectal cancer [100]. It is worth of note that up to 25% of TNBC harbors a g BRCA1/2 mutation and at least 75% and 25% of gBRCA1- and gBRCA2- mutated tumors, respectively, are TNBC [101,102].…”
Section: Hrd and Adaptive Immunity In Breast Cancer: Tmb And Tilsmentioning
confidence: 76%
“…PARP inhibitors, such as olaparib 37,38 or niraparib 39,40 , have shown to be active on brain metastases in patients with homologous recombination deficient (HRD) breast cancer and in murine models of brain metastases 41,42 . Moreover, HRD signatures have been reported to be enriched in breast cancer brain metastases compared with primary tumors 43 , and the occurrence of brain metastases is relatively frequent event in BRCA1/2 mutated cancers 44,45 . In a pancreatic xenograft model, niraparib has shown higher intracranial activity compared with olaparib 41 .…”
Section: (Supplementary Figure S23)mentioning
confidence: 99%